Identificando dispersores-chave e as consequências de sua perda para a dispersão de sementes no Cerrado - Campagnoli, Mariana Lopes (Universidade Federal de São Carlos, 2024)
Seed dispersal is a crucial ecological function influencing the persistence and maintenance of plant populations and communities and depending mostly on frugivorous animals to happen. In the Cerrado, a neotropical savanna, ongoing anthropic pressures associated with land use changes impact frugivore populations, consequently disrupting the seed dispersal services they provide. Identifying plant-frugivore characteristics driving seed dispersal success and understanding how frugivore losses may affect seed dispersal services, can help guide conservation efforts to preserve species interactions and seed dispersal function in the Cerrado. However, to quantify the success of seed dispersal provided by frugivores, we need to include other aspects besides plant-frugivore interaction frequencies. For instance, the number of seeds dispersed, and the probability of each dispersed seed being recruited as a new individual in the population are not considered in most studies. The main goal of this thesis was to understand which plant-frugivore characteristics (at the community- and individuallevels) make interacting partners to be potentially more efficient to seed dispersal, and to understand which potential consequences their losses can bring to seed dispersal in the Cerrado. We recorded interactions using focal observations in plots, videos from camera traps, and birds captured with mist nets. We used seed dispersal effectiveness to estimate seed dispersal success by multiplying interaction frequencies, the number of seeds dispersed per visit and the probability of seeds germinating after interactions. We concluded that frugivore species vary in the number of seeds dispersed per visit, and in the probability of seed germination they provide, highlighting them as important aspects to be incorporated when quantifying frugivore contributions to seed dispersal. Furthermore, we identified that the most abundant plantfrugivore species with highest overlaps in their phenologies had the highest values of seed dispersal effectiveness. We highlight the importance of evaluating the quality of seed dispersal at the individual-level, as well as at the species-level, by detecting that Turdus leucomelas individuals had different contributions to the quality of seed dispersal of Miconia rubiginosa (a key-plant species in the Cerrado). We detected considerable losses in seed dispersal function after the extinction of large-bodied and generalist frugivore species, and after declines in frugivore abundances overall, highlighting the importance of keeping stable populations of frugivores in the Cerrado. Future studies will be crucial to understand the effects of climate change on plant-animal phenology, and its potential cascading effects to seed dispersal. Also, we urgently need studies that include seed deposition patterns and seed dispersal distances as measures of seed dispersal quality, to further understand the role of frugivores in the Cerrado. At last, minimizing the main threats progressing through the Cerrado will be crucial to maintain stable populations of frugivores, as well as the services of seed dispersal and regeneration of plant populations and communities they provide.
Identifying key-dispersers and the consequences of their loss to seed dispersal in the Cerrado
Keywords: Abundância de espécies; Defaunação; Efetividade de dispersão de sementes; Fenologia; Frugívoros de grande porte; Germinação; Generalistas; Variação individual; Defaunation; Germination; Generalists; Individual variation; Large-bodied frugivores; Phenology; Seed dispersal effectiveness; Species abundances; CIENCIAS BIOLOGICAS::ECOLOGIA